Thermoplastic resin composition for denture base
A specific thermoplastic resin composition for dentures, combining a polyester resin with amorphous resins, addresses the weaknesses of conventional thermoplastics by enhancing strength, flexibility, and adhesion, resulting in durable and aesthetically appealing non-metal clasp dentures.
Patent Information
- Application Number
- JP2020173091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-14
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-10-14
AI Technical Summary
Conventional thermoplastic resins used for non-metal clasp dentures lack sufficient strength, flexibility, and adhesion to lining materials, and are prone to scratching and poor polishing properties, making them unsuitable for durable and aesthetically pleasing dentures.
A thermoplastic resin composition comprising 100 parts by mass of a specific polyester resin, polycondensed from a diol component containing spiroglycol and ethylene glycol, and a dicarboxylic acid component with a polycyclic aromatic hydrocarbon skeleton, blended with 5 to 25 parts by mass of an amorphous resin, such as polystyrene or polycarbonate, to enhance flexibility, strength, and adhesion.
The composition provides dentures with high flexibility, impact resistance, and excellent cutting and polishing properties, ensuring high aesthetic quality and suitability for repair and relining with lining materials.
Smart Images

Figure 0007599645000001 
Figure 0007599645000002 
Figure 0007599645000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a denture material suitable for use as a material for the denture base and clasps of a non-metal clasp denture. floor The present invention relates to a thermoplastic resin composition for use. [Background technology]
[0002] In the treatment of missing teeth due to caries, accidents, etc., partial dentures are often used as prosthetic restorations. These partial dentures usually have a denture part in which artificial teeth to replace missing teeth are fixed to a denture base (partial base) that covers the oral mucosa in the missing area, and clasps, which are retention devices for attaching them to clasps made of the adjacent remaining natural teeth so that they do not come off, but they may also have large connectors for connecting bases at distant positions in the dentition to the base or retention device, and small connectors for connecting the clasps to the denture base or large connectors.
[0003] Metal materials are often used for the clasps mentioned above from the viewpoints of strength and durability, but resin materials are sometimes used from the viewpoints of metal allergy countermeasures, aesthetics, wearing comfort, etc. Partial dentures with clasps made of thermoplastic resin materials are also called non-metal clasp dentures (including cases where no metal materials are used at all, as well as cases where metal materials are used partially, such as metal rests and metal frames), and demand for them is increasing due to the advantages mentioned above.
[0004] Conventionally, complete dentures and partial dentures have often used heat-polymerized acrylic resins as well as injection-moldable polymethyl methacrylate (hereinafter referred to as PMMA) resins. In recent years, however, various manufacturers have begun to sell a variety of thermoplastic resins for non-metal clasp dentures, such as polyamide, polyester, and polycarbonate resins, which are also injection-moldable (Non-Patent Document 1).
[0005] Non-metal clasp dentures are required to have the strength to not shift or bend when worn in the oral cavity and chew food, and the flexibility to not break the clasp when dropped outside the oral cavity. For this reason, these new thermoplastic resins are generally more flexible (lower flexural modulus) than heat-polymerized acrylic resins. On the other hand, it has been pointed out that the thermoplastic resins proposed as materials for denture bases and clasps have lower strength (e.g., flexural strength) than heat-polymerized acrylic resins, and that the surface is easily scratched and difficult to polish (Non-Patent Document 1).
[0006] Other physical properties of the above thermoplastic resins tend to vary depending on the resin system, and are selected according to their respective characteristics. For example, polyester resins have a common feature of good adhesion to self-polymerizing resins used for repairing and relining denture bases, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and mucous membrane conditioners, and materials with low bending modulus and high impact resistance have also been developed. However, even within the same resin system, the physical properties vary from material to material, and the specific structure of thermoplastic resins is often not made clear (Non-Patent Document 1).
[0007] Regarding polyester resins used in optical molded products such as food packaging materials and plastic lenses, a polyester resin excellent in heat resistance, transparency, mechanical properties and moldability is known which is obtained by polycondensing a diol component containing 5 mol % or more and 60 mol % or less (hereinafter, "x or more and y or less" may be simply written as "x to y") of a spiro glycol having a specific structure such as 3,9-bis(1,1-dimethyl-2-hydroxyethyl)2,4,8,10-tetraoxaspiro[5.5]undecane (hereinafter sometimes referred to as "SPG") and 30 mol % to 95 mol % of ethylene glycol (however, the above mol % is based on the total amount of spiro glycol and ethylene glycol) and a dicarboxylic acid component containing 80 mol % to 100 mol % of terephthalic acid and / or its ester, and which has a limiting viscosity, melt viscosity, molecular weight distribution and glass transition temperature each within a specified range (Patent Document 1). However, its suitability as a thermoplastic resin for dentures is unclear. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2008-260964 A [Non-patent literature]
[0009] [Non-Patent Document 1] Kenji Fueki et al. "Clinical Application of Partial Dentures Made of Thermoplastic Resin (Non-Metal Clasp Dentures)," Journal of the Japanese Prosthodontic Society, Vol. 5, No. 4, pp. 387-408, 2013 Summary of the Invention [Problem to be solved by the invention]
[0010] In view of the above circumstances, the present invention provides a denture base that can be molded by injection molding, has the characteristics of a polyester resin that is highly flexible and has good adhesion to self-polymerizing resins, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and tissue conditioners, and has higher strength and excellent machinability and polishability than conventional polyester resins for denture bases. floor and a thermoplastic resin material for the denture. floor The object of the present invention is to provide a non-metal clasp denture having clasps made of a molded body of a thermoplastic resin material for dental use. [Means for solving the problem]
[0011] As a result of investigations to solve the above problems, the present inventors found that, among the polyester resins disclosed in Patent Document 1, a polyester resin having a specific structure can solve the above problems, and thus completed the present invention.
[0012] That is, the first aspect of the present invention is a denture floor Used as a material for dentures floor A thermoplastic resin composition for use, comprising: 100 parts by mass of a thermoplastic polyester resin; and 5 to 25 parts by mass of an amorphous thermoplastic resin, The thermoplastic polyester resin is obtained by polycondensation of a diol component (A) and a dicarboxylic acid component (B) in a ratio of 1 mol:1 mol. The deflection temperature under load measured in accordance with the B method of JIS standard K7191-2:2007 is 85 to 125°C, and the Rockwell hardness measured in accordance with the L scale of JIS standard K7202-2:2001 is 90 to 120. A polyester resin comprising: The diol component (A) contains a spiro glycol (A1) having a cyclic acetal skeleton and ethylene glycol (A2), the contents of (A1) and (A2) based on the total number of moles of all diol compounds contained in the diol component (A) are (A1): 15 to 95 mol % and (A2): 5 to 85 mol %, respectively, and the total content of (A1) and (A2) is 20 to 100 mol %, The dicarboxylic acid component (B) contains a dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton and / or an ester (B1') thereof, the total content of the (B1) and the (B1') is 15 to 100 mol % based on the total number of moles of all dicarboxylic acid compounds contained in the dicarboxylic acid component (B), The amorphous thermoplastic resin is at least one selected from the group consisting of polyvinyl chloride, polystyrene, polymethyl methacrylate, acrylonitrile-butadiene-styrene copolymer resin, polycarbonate, modified polyphenylene ether, and glycol-modified polyethylene terephthalate. It consists of: The deflection temperature under load measured according to JIS K7191 Method A is in the range of 60 to 150°C. A denture characterized by floor It is a thermoplastic resin composition for use.
[0013] The denture of the first embodiment of the present invention floor The above-mentioned "polyester resin obtained by polycondensing a diol component (A) and a dicarboxylic acid component (B) in a ratio of 1 mole:1 mole" (hereinafter also referred to as "specific polyester"), which constitutes the main component of the thermoplastic resin composition for dentures (hereinafter also referred to as "thermoplastic resin composition for dentures of the present invention"), is defined as above from the viewpoint of the diol component (A) and the dicarboxylic acid component (B) which are the raw materials, but can also be expressed as follows when specified from the viewpoint of the structure derived from each component. That is, it can also be defined as "a polyester resin in which the number of structural units derived from a spiro glycol (A1) having a cyclic acetal skeleton is 15 to 95%, the number of structural units derived from an ethylene glycol (A2) is 5% to 85%, and the total number of both units is 20 to 100% or less, based on the total number of structural units derived from the diol component, and the total number of structural units derived from a dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton and its ester (B1') is 15 to 100% based on the total number of structural units derived from the dicarboxylic acid component".
[0014] In the thermoplastic resin composition for dentures of the present invention, the specific polyester is preferably such that the dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton is naphthalene dicarboxylic acid. The resin is made of at least one material selected from the group consisting of polystyrene, polymethyl methacrylate, and acrylonitrile-butadiene-styrene copolymer resin, and is soluble in ethyl acetate. It is preferred.
[0015] A second form of the present invention is a non-metal clasp denture having a denture part with artificial teeth fixed to a partial base and clasps for attaching the denture part to clasps, wherein at least a portion of the partial base and the clasps are made of a molded article of the thermoplastic resin composition for dentures of the present invention. Effect of the Invention
[0016] The thermoplastic resin composition for dentures of the present invention can be used to form a denture base by injection molding, has high flexibility, and has particularly good adhesion to self-polymerizing resins, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and tissue conditioners. It also has the advantages of being high strength and excellent cuttability and polishability.
[0017] Furthermore, non-metal clasp dentures made using the thermoplastic resin composition for dentures of the present invention have excellent impact resistance due to their moderate flexibility and are less likely to break, as well as being strong and having a highly aesthetic appearance with a smooth and glossy surface.Furthermore, they are suitable for repair and relining using self-polymerizing resins, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and mucous membrane conditioners. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] As a result of investigations to solve the above-mentioned problems, the inventors have found that, among the various polyester resins available, the specific polyester not only has the characteristics of conventional polyester resins for denture bases, such as the ability to be molded into a denture base by injection molding, high flexibility, and good adhesion to various lining materials, but also has the further characteristics of high strength and excellent machinability and polishability, and have already proposed this as a new polyester resin for denture bases (Patent Application No. 2019-108422).
[0019] The specific polyester is different from the polyester resin described in Patent Document 1 in that a benzene ring is introduced as a skeleton derived from a dicarboxylic acid in the form of multiple condensed rings, rather than a single ring, which increases the rigidity of the resin and improves the deflection temperature under load and Rockwell hardness. These improvements in physical properties improve the machinability and abrasion resistance, making it suitable as a denture base material that is less susceptible to loss of transparency due to cutting. That is, when cutting in a dry cutting process, the heat applied to the denture base is at least 50°C, and when cutting the same place for a long time, it rises to about 70°C to 80°C. For this reason, when the deflection temperature under load is low, the resin softens and adheres to the cutting bar or denture base, reducing the machinability, and even during polishing, the resin softened by heat remains on the surface, reducing the gloss. In addition, when the Rockwell hardness is low, deformation due to overcutting or deflection of the resin is likely to occur due to the load from the cutting bar, and further polishing scratches are likely to occur on the surface due to polishing sand. In contrast, the specific polyester has improved machinability and polishability due to the improved rigidity of these resins.
[0020] The present invention was made based on the result of further investigation into dentures using the specific polyester having such excellent characteristics as a denture base material, and the discovery that the adhesiveness to the lining material during lining treatment is further improved by blending a specific amorphous thermoplastic resin within a certain range. That is, the adhesive strength between the denture base made of the specific polyester and the lining material was about 5 to 6 MPa, but when a resin composition containing 5 to 25 parts by mass of at least one amorphous thermoplastic resin selected from the group consisting of polyvinyl chloride (PVC), polystyrene (PS), polymethyl methacrylate (PMMA), acrylonitrile-butadiene-styrene copolymer resin (ABS), polycarbonate (PC), modified polyphenylene ether (m-PPE) and glycol-modified polyethylene terephthalate (PET-G) per 100 parts by mass of the specific polyester is used as a denture base material, the adhesive strength is improved to 10 MPa or more. The reason for this effect is believed to be that the primer used in the backing treatment is given solubility or swelling properties in ethyl acetate, which is commonly contained as a solvent, and the roughening caused by the primer treatment increases adhesion to the backing material.
[0021] The specific polyester and the specific amorphous resin which are the main components of the thermoplastic resin for dentures of the present invention will be described below, and then the thermoplastic resin for dentures of the present invention will be described in detail.
[0022] 1. Specific polyester The specific polyester is a polyester resin suitable for use as a material for denture bases, and is obtained by polycondensing a diol component and a dicarboxylic acid component in a ratio of 1 mol:1 mol, similar to conventional polyester resins. The specific polyester is characterized in that each of these components has a specific composition. That is, the diol component includes spiro glycol (A1) and ethylene glycol (A2) having a cyclic acetal skeleton, and the contents of (A1) and (A2) based on the total number of moles of all diol compounds contained in the diol component (A) must be (A1): 15 to 95 mol% and (A2): 5 to 85 mol%, respectively, and the total content of (A1) and (A2) must be 20 to 100 mol%. The dicarboxylic acid component contains a dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton and / or an ester (B1') thereof, and the total content of the (B1) and the (B1') based on the total number of moles of all dicarboxylic acid compounds contained in the dicarboxylic acid component (B) needs to be 15 to 100 mol %.
[0023] In other words, the specific polyester is a polyester resin obtained by polycondensing a diol compound and a dicarboxylic acid compound in a ratio of 1:1, characterized in that, based on the total number of structural units derived from the diol compounds in the polyester resin, the number of structural units derived from a spiro glycol (A1) having a cyclic acetal skeleton is 15 to 95%, the number of structural units derived from ethylene glycol (A2) is 5 to 85%, and the total number of both units is 20 to 100%, and based on the total number of structural units derived from the dicarboxylic acid compounds in the polyester resin, the number of structural units derived from a dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton is 15 to 100%.
[0024] 1-1. Diol component (A) The specific polyester is characterized in that it has excellent heat resistance, transparency, moldability, and mechanical properties as a resin by containing a spiro glycol (A1) having a cyclic acetal skeleton in the diol component (A). The content of the spiro glycol (A1) having a cyclic acetal skeleton in the diol component (A) may be 15 to 95 mol%, preferably 30 to 80 mol%, more preferably 40 to 65 mol%.
[0025] The content of ethylene glycol (A2) may be 5 to 85 mol %, preferably 10 to 70 mol %, particularly preferably 15 to 55 mol %, and the lower limit of the total content of (A1) and (A2) is 20 mol % or more, preferably 40 mol % or more, particularly preferably 55 mol % or more, and the upper limit is always 100 mol % or less.
[0026] The spiro glycol (A1) having a cyclic acetal skeleton means a compound represented by the structural formula 1 {bis(hydroxypivalaldehyde) pentaerythritol acetal cyclic acetal: CAS No. 1455-42-1}.
[0027] [ka]
[0028] Furthermore, the diol component (A) is preferably composed of only the (A1) and (A2), but may contain diol compounds other than the spiro glycol (A1) and ethylene glycol (A2) having a cyclic acetal skeleton (hereinafter also referred to as "other diol compounds") as the remaining components when the total content of the two is less than 100 mol% depending on the content of these components. Also, depending on the type of other diol compound, when a specific "other diol compound" such as cyclohexane dimethanol is used, the effect may be higher when the content of the compound is higher than the content of the (A2). In such a case, the content of the "other diol compound" is preferably 35 to 60 mol%, particularly 40 to 50 mol%. However, from the viewpoint of effect, the content of the (A1) tends to be preferably 40 to 65 mol%, so when the "other diol compound" as described above is contained, it is preferable to contain it so as to replace a part of the (A2) while keeping the content of the (A1) within this range.
[0029] Examples of the "other diol compounds" that can be used include aliphatic diols such as trimethylene glycol, 2-methylpropanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, and neopentyl glycol; polyether compounds such as polyethylene glycol, polypropylene glycol, and polybutylene glycol; 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,2-decahydronaphthalenedimethanol, 1,3-decahydronaphthalenedimethanol, 1,4-decahydronaphthalenedimethanol, 1,5-decahydronaphthalenedimethanol, 1,6-decahydronaphthalenedimethanol, and 2,7-decahydronaphthalenedimethanol. Examples of the alkylene oxide adducts include alicyclic diols such as ethanol, tetralin dimethanol, norbornane dimethanol, tricyclodecane dimethanol, 5-methylol-5-ethyl-2-(1,1-dimethyl-2-hydroxyethyl)-1,3-dioxane, and pentacyclododecane dimethanol; alkylene oxide adducts of bisphenols such as 4,4'-(1-methylethylidene)bisphenol, methylene bisphenol (bisphenol F), 4,4'-cyclohexylidene bisphenol (bisphenol Z), and 4,4'-sulfonyl bisphenol (bisphenol S); and alkylene oxide adducts of aromatic dihydroxy compounds such as hydroquinone, resorcinol, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, and 4,4'-dihydroxydiphenylbenzophenone. Among these, it is preferable to use at least one selected from the group consisting of 1,3-propanediol, 1,4-butanediol, neopentyl glycol, and 1,4-cyclohexanedimethanol because this improves processability.
[0030] 1-2. Dicarboxylic acid component (B) The dicarboxylic acid component (B) contains a dicarboxylic acid (B1) having a polycyclic aromatic hydrocarbon skeleton and / or an ester (B1') thereof. Moreover, the total content of the (B1) and the (B1') based on the total number of moles of all dicarboxylic acid compounds contained in the dicarboxylic acid component (B) must be 15 to 100 mol %. This improves the rigidity of the resin, and provides good machinability and polishability. The lower limit of the total content of the (B1) and the ester (B1') thereof in the dicarboxylic acid component (B) is preferably 25 mol % or more, particularly preferably 50 mol % or more.
[0031] Here, examples of the dicarboxylic acid (B1) having a polycyclic aromatic hydrocarbon skeleton include dicarboxylic acids having a polycyclic aromatic hydrocarbon skeleton in the molecule, such as naphthalene, anthracene, naphthacene, pentacene, benzopyrene, chrysene, pyrene, triphenylene, corannulene, coronene, ovalene, etc., and esters thereof. Among these, it is preferable to use naphthalenedicarboxylic acid from the viewpoint of biological safety.
[0032] The substitution positions of the dicarboxylic acid in naphthalenedicarboxylic acid are not particularly limited, but naphthalenedicarboxylic acid in which each aromatic ring is substituted with a carboxylic acid is preferred, and 2,6-naphthalenedicarboxylic acid is particularly preferred.
[0033] The ester (B1') of the dicarboxylic acid (B1) having the polycyclic aromatic hydrocarbon skeleton is a compound capable of forming a polyester resin by transesterification with the diol component, and means an ester of the alcohol compound eliminated during the transesterification with the (B1). As the alcohol compound, a monohydric alcohol having 1 to 6 carbon atoms is usually used. As (B1), for the same reason as above, an ester of naphthalenedicarboxylic acid is preferred, and examples of the ester include dimethyl naphthalenedicarboxylate, dipropyl naphthalenedicarboxylate, diisopropyl naphthalenedicarboxylate, dibutyl naphthalenedicarboxylate, and dicyclohexyl naphthalenedicarboxylate.
[0034] The dicarboxylic acid component (B) may also contain a dicarboxylic acid compound other than (B1) and / or its ester (hereinafter also referred to as "other dicarboxylic acid compounds, etc."). Examples of the "other dicarboxylic acid compounds, etc." include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2-methylterephthalic acid, biphenyldicarboxylic acid, and tetralindicarboxylic acid; aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, decalindicarboxylic acid, norbornanedicarboxylic acid, tricyclodecanedicarboxylic acid, and pentacyclododecanedicarboxylic acid; and esters thereof. Among them, it is preferable to use aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2-methylterephthalic acid, biphenyldicarboxylic acid, and tetralindicarboxylic acid, and esters thereof, and it is more preferable to use isophthalic acid, terephthalic acid, and esters thereof.
[0035] 1-3. Polycondensation method The method of polycondensing the diol component (A) and the dicarboxylic acid component (B) in a ratio of 1 mole:1 mole can be any of the melt polymerization methods or solution polymerization methods such as transesterification and direct esterification, which are known as conventional methods for producing polyester resins, without any particular limitations. For example, the method disclosed in Patent Document 1, which is a method for producing the "polyester resin obtained by polycondensing a specific diol component containing SPG and the like with a specific dicarboxylic acid component," can be suitably carried out by applying the method disclosed in Patent Document 1 to the raw material system of the present invention.
[0036] Incidentally, Patent Document 1 states with regard to the above-mentioned production method that "for example, melt polymerization methods such as transesterification and direct esterification or solution polymerization methods can be mentioned. Conventionally known transesterification catalysts, esterification catalysts, etherification inhibitors, polymerization catalysts used in polymerization, various stabilizers such as heat stabilizers and light stabilizers, polymerization regulators, and the like can also be used. Examples of transesterification catalysts include compounds of manganese, cobalt, zinc, titanium, calcium, and the like. Examples of esterification catalysts include compounds of manganese, cobalt, zinc, titanium, calcium, and the like. Examples of etherification inhibitors include amine compounds. Examples of polycondensation catalysts include compounds of germanium, antimony, tin, titanium, and the like. It is also effective to add various phosphorus compounds such as phosphoric acid, phosphorous acid, and phenylphosphonic acid as heat stabilizers. Other additives such as light stabilizers, antistatic agents, lubricants, antioxidants, mold release agents, and the like may also be added. The timing of addition of SPG is not particularly limited, and it may be added after the completion of the esterification reaction or transesterification reaction. At that time, in the direct esterification method, water may be added to improve the slurry properties."
[0037] The polyester resin (specific polyester) thus produced is pelletized or powdered by a conventional method for use. For example, when pelletizing, the polyester resin is molded into strands of a certain thickness using a kneader or extrusion molding machine, and then cut into pellets of a certain length using a cutter, pelletizer, pulverizer, or the like.
[0038] 1-4. How to check for specific polyester Among the polyester resins obtained by the above-mentioned method, there are some that are available as resin materials in a pelletized or powdered state (although it is not known that such resin materials can be used as denture base materials), and these may also be considered as specific polyesters. Whether or not a polyester resin corresponds to a specific polyester can be determined by examining a solution dissolved in deuterated chloroform. 1 It can also be confirmed by performing H-NMR measurement, assigning the peaks, and then calculating the content ratio of each component from the integrated value of the peaks.
[0039] For reference, the peak assignments for each component are shown below.
[0040] Ethylene glycol derived (δ=4.70 4H) - From spiroglycol (δ=4.52 2H, δ=4.32 2H, δ=4.19 4H, δ=3.54 4H, δ=3.32 2H, δ=1.04 12H) Cyclohexanedimethanol {δ=4.29(cis), 4.19(trans) 4H, δ=2.05(cis), 1.80(trans) 2H, δ=1.94(trans), 1.14(cis) 4H, δ=1.66(cis), 1.56(trans) 4H} Terephthalic acid derived (δ=8.10 4H) -Derived from naphthalenedicarboxylic acid (δ=8.62 2H, δ=8.12 2H, δ=8.03 2H).
[0041] Furthermore, in thermoplastic resins, the physical properties often vary depending on the dispersion state of copolymerization units in the molecule, the molecular weight distribution, etc., but it is difficult to analyze these to define the structure of a thermoplastic resin in detail, so resins are often defined by the range of physical property values, etc.
[0042] In the specific polyester, among the polyester resins obtained by the above-mentioned method, a polyester resin having a deflection temperature under load measured in accordance with the B method of JIS standard K7191-2:2007 (ISO75-2:2004) of 85°C or more and 125°C or less, and a Rockwell hardness measured in accordance with the L scale of JIS standard K7202-2:2001 (ISO2039-2:1987) of 90 or more and 120 or less, is used because of the high effect described above. Using .
[0043] 2.Specified amorphous resin Next, the amorphous thermoplastic resin (specific amorphous resin) used in the thermoplastic resin for dentures of the present invention will be described.
[0044] 2-1. Amorphous thermoplastic resin Amorphous thermoplastic resins are thermoplastic resins that do not have regularly arranged crystalline parts in the molecular structure when solidified, but have a random structure in which the molecules are irregularly entangled. Commonly known amorphous thermoplastic resins include polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polystyrene (PS), polymethyl methacrylate (PMMA), acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate (PC), modified polyphenylene ether (m-PPE), polyethersulfone (PES or PESU), polyetherimide (PEI), polyamideimide (PAI), and polysulfone (PSF or PSU). Other examples of amorphous resins include glycol-modified polyethylene terephthalate (PET-G), which is an improved version of polyethylene naphthalate (PET), which is usually known to be crystalline, by adding cyclohexanedimethanol, and polyarylate (PAR), which uses bisphenol A as a diol component instead of ethylene glycol. Cycloolefin polymer (COP) is also an amorphous resin.
[0045] 2-2.Specified amorphous resin In the thermoplastic resin composition for dentures of the present invention, at least one type selected from the group consisting of polyvinyl chloride (PVC), polystyrene (PS), polymethyl methacrylate (PMMA), acrylonitrile-butadiene-styrene copolymer resin (ABS), polycarbonate (PC), modified polyphenylene ether (m-PPE), and glycol-modified polyethylene terephthalate (PET-G) is used as the specific amorphous resin.
[0046] These specific amorphous resins are often soluble or swellable in ethyl acetate, which is contained as a solvent in primers and adhesives, which are pretreatment agents when performing backing treatment, and therefore it is believed that the inclusion of the specific amorphous resin improves adhesion to the backing material. For this reason, it is preferable to use a specific amorphous resin that is soluble or swellable in ethyl acetate. Here, solubility or swelling in ethyl acetate means that when a molded body of an amorphous thermoplastic resin is immersed in an excess amount of ethyl acetate and left at 37°C, the shape of the molded body changes due to swelling or dissolution. Whether or not a resin has solubility or swelling in ethyl acetate can be confirmed, for example, as follows. That is, it can be confirmed by visually observing one pellet of an amorphous thermoplastic resin with a pellet diameter and / or pellet length of about 3 to 5 mm after immersing it in 1 ml of ethyl acetate at 37°C for 24 hours. In general, when a resin molded product is immersed in a solvent and left, no change occurs if the resin does not have swelling and solubility in the solvent. Furthermore, when a resin is dissolved in a solvent, it generally goes through the following process: the resin molded product becomes cloudy → the resin molded product swells (increases in apparent volume) → the shape of the resin molded product collapses → it dissolves. Therefore, if the above visual observation shows that the volume has clearly increased due to swelling, that the shape has collapsed due to dissolution, or that the resin molded product is completely dissolved, it is determined that the resin molded product has solubility or swelling properties, whereas if there is no change or the pellets are simply cloudy, it is determined that the resin molded product does not have solubility or swelling properties.
[0047] From the viewpoint of compatibility or blendability with the specific polyester, the specific amorphous resin is one whose deflection temperature under load measured according to ISO75 (JIS K7191) Method A (1.8 MPa) is in the range of 60 to 150°C. Using When the deflection temperature under load of the specific amorphous resin is within this range, it can be easily homogenized during blending (melting and kneading).
[0048] 3. Thermoplastic resin composition for dentures of the present invention The thermoplastic resin composition for dentures of the present invention is a thermoplastic resin composition used exclusively as denture parts such as denture bases and clasps, and contains 5 to 25 parts by mass of a specific amorphous resin per 100 parts by mass of a specific polyester. By having such a composition, it is possible to improve the adhesion to a lining material without impairing the characteristics of the specific polyester. Since it is necessary to express adhesion while minimizing the impairment of the inherent physical properties of the specific polyester, the blending amount of the specific amorphous resin is preferably 5 to 20 parts by mass, and particularly preferably 10 to 15 parts by mass.
[0049] The thermoplastic resin component contained in the thermoplastic resin composition for dentures of the present invention preferably consists of only the specific polyester and the specific amorphous resin, but other thermoplastic resins may also be contained within a range that does not inhibit the curing of the present invention. In addition, as components other than the resin, coloring materials such as pigments and dyes, fillers such as inorganic fillers and organic fillers, release agents, ultraviolet absorbers, light stabilizers, antioxidants, lubricants, flame retardants, antistatic agents, etc. may be appropriately blended.
[0050] The thermoplastic resin composition for dentures of the present invention may be a mixture of powder or pellets of a specific polyester, powder or pellets of a specific amorphous resin, and various additives (usually powders) such as pigments that are blended as necessary, but it is preferable to melt-knead them and use them in powder or pellet form. For melt-kneading, a device such as a heated twin-screw extrusion kneader is generally used. For example, the mixture prepared in advance is fed into the feeder of a twin-screw extrusion kneader, and kneaded at a screw rotation speed of 50 to 150 rpm, for example, by setting the barrel temperature to 270°C to 280°C. The screw configuration is appropriately configured by combining a feed screw that feeds the resin and a kneading disk that kneads by applying a shear force. The resin kneaded in this way is pelletized or powdered by a conventional method for use. For example, when pelletizing, the resin is molded into strands of a certain thickness using a device such as a kneader or extrusion molding machine, and then cut into small pieces of a certain length using a cutter, pelletizer, pulverizer, or the like to form pellets.
[0051] The thermoplastic resin for dentures of the present invention not only has the characteristics of conventional polyester resins for denture bases, such as the ability to form a denture base by injection molding, high flexibility, and good adhesion to immediate polymerization resins, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and tissue conditioners, but also has the characteristics of high strength and excellent machinability and polishability. Therefore, the plate denture of the present invention having a denture base manufactured using the thermoplastic resin for dentures of the present invention, and the non-metal clasp denture of the present invention, whose denture base and clasp parts are formed from the thermoplastic resin for dentures of the present invention, have the characteristics of being excellent in impact resistance due to moderate flexibility and unlikely to break, as well as being high in strength and having a high aesthetic appearance with a smooth and glossy surface, and being suitable for repair and relining using immediate polymerization resins, (meth)acrylate-based hard lining materials, silicone-based soft lining materials, and tissue conditioners.
[0052] 4. Non-metal clasp denture and its manufacturing method according to the present invention A non-metal clasp denture is a type of partial denture (partial denture) that belongs to the category of dentures with a denture base, and has a denture part in which artificial teeth to replace missing teeth are fixed to a denture base (partial) that covers the oral mucosa in the missing area, and clasps that are retention devices for attaching the artificial teeth to the adjacent remaining natural teeth so that they do not come off. In non-metal clasp dentures, the clasps are made of non-metallic materials such as thermoplastic resin materials. However, this does not completely reject the use of metallic materials, and parts other than the clasps may include components made of metallic materials such as metal rests and metal frames.
[0053] The non-metal clasp denture of the present invention has a denture portion with artificial teeth fixed to a partial base, and clasps for attaching the denture portion to clasps, and is characterized in that at least a portion of the partial base and the clasps are made of a molded article of the thermoplastic resin composition for dentures of the present invention.
[0054] In the non-metal clasp denture of the present invention, it is sufficient that the clasps and / or at least a portion of the denture base are made of this thermoplastic resin material, but it is preferable that both the clasps and the resin denture base are made of this thermoplastic resin material and that they are formed as a single unit.
[0055] The non-metal clasp denture of the present invention can be suitably manufactured by a manufacturing method including an injection molding step of forming at least a portion of the clasp and / or the denture base by injection molding the thermoplastic resin material.
[0056] The injection molding process is not particularly different from the manufacturing method of a non-metal clasp denture by injection molding using a conventional thermoplastic resin, except that the thermoplastic resin material is used as the raw resin for injection molding, and for example, a method can be adopted in which a plaster mold made based on an intraoral impression taken from a patient is used as a mold, the mold is set in an injection molding machine, the thermoplastic resin material that has been heated and softened is injected into the mold, and the mold is cooled and then removed from the mold. When a mold that does not have a part that will become a clasp part is used, a plate denture of the present invention that does not have a clasp part can be manufactured, and when a mold that has a part that will become a clasp part is used, a non-metal clasp denture of the present invention can be manufactured.
[0057] The above method will be specifically described below. That is, in the above method, in order to prepare a mold, first, plaster is poured into an impression of the shape of the patient's oral cavity, which is taken using a silicone-based impression material, an alginate-based impression material, or an agar impression material, to prepare a plaster model imitating the shape of the patient's oral cavity. Next, after the design of the base plate is applied to the obtained plaster model, a hardening composition called a self-polymerizing resin is pressed against the design line on the model, and a base plate (with clasps as necessary) is prepared on the plaster model. Then, dental paraffin wax is piled like a bank on the base plate to prepare a part called a wax bank where artificial teeth are arranged, and the base plate with the wax bank formed is removed from the stone model to form a bite plate. This bite plate is attached to the patient's oral cavity, a bite registration is performed, and the bite plate is adjusted. After adjustment, the occlusion plate is set back on the plaster model and attached to an articulator, the jaw movement and occlusion state in the oral cavity are reproduced, and artificial teeth are arranged on the wax ridge to create a wax denture (artificial teeth arranged on the occlusion plate). The resulting negative model of the wax denture becomes the mold for injection molding.
[0058] The above mold is usually made through a three-stage embedding operation as described below. That is, first, a plaster model and a wax denture set in it are placed in the lower part of the flask of a dental injection molding machine, and then the primary embedding is performed in which the plaster model alone is embedded and the wax denture is above the flask, and mixed plaster is poured in and hardened. Next, the mixed plaster is piled up so as to cover the wax denture, and the secondary embedding is performed. After that, the upper part of the flask is fitted to the lower part of the flask and the lid is put on, and the mixed plaster is poured in through the hole in the upper part of the flask, and the tertiary embedding is performed. Then, after the plaster of the tertiary embedding hardens, the upper and lower parts of the flask are separated, and the base plate and the wax bank are removed. If the wax bank is difficult to remove, hot water is poured over it to dissolve it. Then, only the artificial tooth is embedded in the plaster. The upper part of the flask is fitted to the lower part of the flask again, and the resulting product is in a sealed state, which becomes the mold.
[0059] Injection molding is performed by supplying pellets of the thermoplastic resin material, which have been vacuum-dried to remove moisture, to an injection molding machine in which the above-mentioned mold is set. Specifically, the required amount of the thermoplastic resin material is supplied, and the pellets are melted by heating in the resin melting section of the injection molding machine at a temperature range of about 150°C to 400°C for about 5 to 60 minutes, and then an air pressure of 0.1 to 2.0 MPa is applied to the injection molding machine by an air compressor to inject the molten resin, filling the resin inside the set flask (mold). After the resin cools and hardens, the flask is divided and the plaster is divided using a mallet or the like, and the denture (real denture) in which the resin and the artificial tooth are integrated is taken out.
[0060] Since burrs are attached to the entire circumference of the removed denture, it is cut with a stamp bar or resin point while protecting the base edge. The surface cut with the points is polished with a sandpaper cone from medium to fine among the coarse, medium, and fine types, and then polished with a lathe. Polishing with a lathe is done by first using a felt cone and polishing sand, then a hard bristle brush and polishing sand in that order to make the surface smooth, then rinsing thoroughly with water before moving on to the finish polishing. The surface is polished by using a soft bristle brush and zinc oxide, then a cloth buff and an abrasive in that order. The lathe is used at a low rotation speed to prevent the polished surface from drying out and generating heat. Then, by fitting it to the oral cavity and making final adjustments, the finished product, the plate denture of the present invention or the non-metal clasp denture of the present invention, can be obtained. EXAMPLES
[0061] In order to specifically explain the present invention, examples and comparative examples will be given, but the present invention is not limited to these in any way.
[0062] 1. Reference Examples 1 to 4 and Reference Comparative Examples 1 to 7 First, the specific polyester, which is the main component of the thermoplastic resin composition of the present invention, is excellent as a polyester resin for denture base, and will be described with reference to reference examples and reference comparative examples.
[0063] The commercially available thermoplastic resins A to K shown below were analyzed to determine whether they were specific polyesters, and then the deflection temperature under load, Rockwell hardness, machinability, and polishability of each thermoplastic resin were measured and evaluated. The details are shown below.
[0064] 1-1.Thermoplastic resin A: Altesta S1000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) B: Altesta S2000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) C: Altesta S3000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) D: Altesta S4500 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) E: Altesta SN1500 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) F: Altesta SN3000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) G: Altesta SN4500 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) H: Altesta SH (manufactured by Mitsubishi Gas Chemical Co., Ltd.) I: Acryshot (manufactured by Yamahachi Dental Materials Co., Ltd.: PMMA resin for denture base) J: Estheshot (made by iCast Co., Ltd.: PET resin for denture base) K: Estheshot Bright (made by iCast Co., Ltd.: polyester resin for denture base)
[0065] 1-2. Judgment as to whether or not a material falls under specific polyester (1) Thermoplastic resin I Thermoplastic resin I is an acrylic resin commercially available for use in denture bases and does not fall under the category of specific polyesters.
[0066] (2) Thermoplastic resins (polyester resins) A to H, J and K The various Artesta resins, thermoplastic resins A to H, are polyester resins sold by Mitsubishi Gas Chemical Co., Ltd., and are said to be usable for applications such as display sheets and films, food containers, sealant films, beverage containers, cosmetic containers, pharmaceutical containers, seasoning bottles, miscellaneous goods and stationery, and protective covers. Thermoplastic resins J and K are polyester resins commercially available for use in denture bases.
[0067] These thermoplastic resins (polyester resins) A to H, J, and K were analyzed as follows to determine whether they were specific polyester resins. That is, a pellet of each resin was immersed in 1 ml of deuterated chloroform (containing tetramethylsilane as an internal standard) and left at 37°C for 6 hours to completely dissolve it, and the solution was transferred to an NMR tube. 1 H-NMR measurements were performed. The measurements were performed using a JEOL RESONANCE JNM-ECA 400II model, with 16 cumulative measurements at 400 MHz. After peak assignments were performed on the obtained NMR charts, those in which no peaks attributable to SPG were confirmed were determined to be non-specific polyester resins that do not fall under specific polyesters, and those in which peaks attributable to spiroglycol (SPG) were confirmed were determined to be non-specific polyester resins that do not fall under specific polyesters, and the content ratios of each component were calculated from the integral values of the peaks attributable to terephthalic acid (TPA), 2,6-naphthalenedicarboxylic acid (NDCA), ethylene glycol (EG), spiroglycol (SPG), and 1,4-cyclohexanedimethanol (CHDM). The analysis results are shown in Table 1.
[0068] From Table 1, it can be seen that thermoplastic resins (polyester resins) A to D, J, and K (for J and K, no peaks derived from naphthalenedicarboxylic acid were confirmed) are non-specific polyester resins that do not fall under the category of specific polyesters, and that thermoplastic resins (polyester resins) E to H fall under the category of specific polyesters.
[0069] [Table 1]
[0070] 1-3. Measurement methods and evaluation criteria for various physical properties of thermoplastic resins A to K (1) Heat deflection temperature (HDT) measurement A smooth test piece with no air bubbles and measuring 10mm x 80mm x 4mm was prepared using a hot press machine (IMC-11D2-C, manufactured by Imoto Manufacturing Co., Ltd.) and a SUS mold. The deflection temperature under load (℃) was measured in accordance with JIS standard K7191-2:2007 (ISO75-2:2004). The conditions were B method, applying a load of 0.45MPa, and the flatwise method. The HDT test device S6-MH, manufactured by Toyo Seiki Co., Ltd., was used for the measurement.
[0071] (2) Rockwell hardness (HRL) measurement Using a hot press (Imoto Manufacturing Co., Ltd., IMC-11D2-C) and a SUS mold, smooth test pieces with no air bubbles, 20 mm square and 6 mm thick, were prepared, and Rockwell hardness (HRL) was measured on the L scale with a test load of 588.4 N and a steel ball indenter diameter of 6.35 mm in accordance with JIS standard K7202-2:2001 (ISO2039-2:1987). The measurements were performed using Akashi's AR-10, with three test pieces per sample, three measurements per test piece, and the average of all nine measurements was taken as the Rockwell hardness (HRL).
[0072] (3) Bending strength measurement The resin was molded into a plate of 15 mm x 30 mm and 2 mm thick using a hot press machine (IMC-11D2-C, manufactured by Imoto Manufacturing Co., Ltd.) and a SUS mold. The molded body was cut into 2 mm pieces using a precision cutting machine (Isomet LS, manufactured by Buhler Co., Ltd.) to prepare test pieces of 2 mm x 2 mm x 30 mm. The dimensions were measured and the pieces were immersed in ion-exchanged water at 37°C for one week and used for the bending test. The bending test was performed by setting the test pieces in a precision universal testing machine (AG-Xplus50kN, manufactured by Shimadzu Corporation) with a support distance of 20 mm and a crosshead speed of 1 mm / min. Measurements were performed on five test pieces per sample, and the average value was taken as the bending strength (MPa).
[0073] (4) Machinability evaluation Various resins were vacuum dried, and a block-shaped molded body of 10 mm x 10 mm x 12 mm was obtained using an injection molding machine for dental laboratories (Yamahachi Dental Materials Co., Ltd., Pro-Jet II). A cutting pin was attached to this molded body, which was then attached to a dry cutting machine (Roland DG Corporation, DWX-50), and the molded body was cut into a crown shape using a cutting bar (Yamahachi Dental Materials Co., Ltd., CAD / CAM milling bar, diamond-coated type, φ2 mm, φ0.8 mm). The state during cutting and the size of the cutting debris were observed and evaluated. A dry cutting machine was used because dental technicians usually cut and polish denture bases using a dry method.
[0074] The evaluation criteria for machinability are shown below. ◎: No problems with cutting. The cutting debris is very fine and does not stick to the cutting bar. ○: Cutting possible. The cutting waste is large and twisted, but the cutting waste does not stick to the cutting bar and can be cut. △: Problems with cutting. The resin melts onto the cutting bar many times during cutting, but the cut object is completed. ×: Cutting not possible. A large amount of resin was welded to the cutting bar during cutting, making it impossible to continue cutting.
[0075] (5) Abrasiveness evaluation Three resin test pieces were prepared for each sample by molding them into 20 mm squares and 4 mm thick using a hot press machine (IMC-11D2-C, Imoto Manufacturing Co., Ltd.), and attached to the bottom of the sample holder for the automatic polishing machine with double-sided tape in a position where force was applied evenly to three points. The holder was set in an automatic rotary polishing machine (Automet250&Ecomet250, Buhler Co., Ltd.), and polishing was performed for 30 seconds with waterproof abrasive paper #800, 30 seconds with #1500, 60 seconds with #3000, and 60 seconds with Baicalox liquid abrasive (alumina suspension 0.3 um) applied to a buff polishing cloth. The automatic rotary polishing machine was set under the following conditions: head rotation speed 40 rpm, base rotation speed 300 rpm, and total load 6 Lbs. The polished surface of the test piece was observed visually and with a laser microscope (Keyence Corporation, VK-9700) and evaluated. The objective lens of the laser microscope used was 20x. The evaluation criteria are as follows:
[0076] : A smooth polished surface is formed, and there are almost no polishing scratches even when observed with a laser microscope. ◯: A smooth polished surface was formed when observed visually, but polishing scratches were found in some areas when observed with a laser microscope. △: A smooth polished surface was formed when observed visually, but polishing scratches were found at a fairly high frequency when observed with a laser microscope. ×: Numerous polishing scratches are visible to the naked eye. When observed with a laser microscope, numerous polishing scratches, from large to small, are present.
[0077] 1-4. Measurement and evaluation results The measurement and evaluation results for thermoplastic resins A to K are summarized in Table 2.
[0078] [Table 2]
[0079] As shown in Table 2, thermoplastic resins E to H (Reference Examples 1 to 4) corresponding to specific polyesters all had good physical properties, such as a deflection temperature under load (HDT) of 85°C or more, a Rockwell hardness (HRL) of 90 or more, a flexural strength of 99 MPa or more, a machinability evaluation of ○, and a polishability evaluation of ○. In particular, thermoplastic resin H, which contains only naphthalenedicarboxylic acid as the dicarboxylic acid component and cyclohexanedimethanol as the third diol component, showed the highest values for the deflection temperature under load, Rockwell hardness, and flexural strength.
[0080] On the other hand, thermoplastic resins A to D (Reference Comparative Examples 1 to 4), which are polyester resins but contain only terephthalic acid as a dicarboxylic acid component and do not use a dicarboxylic acid compound (B1) and / or its ester (B1') having a polycyclic aromatic hydrocarbon skeleton and therefore do not fall under the category of specific polyesters, did not have a Rockwell hardness of 90 or more and also had lower bending strengths than the Reference Examples. In addition, the machinability was all rated as x, with a large amount of resin melting onto the cutting bar, making it impossible to continue cutting, and the polishability was all rated as △.
[0081] Moreover, I (Reference Comparative Example 5), which is a PMMA resin for denture base, was rated as excellent in machinability and polishability, but had the lowest bending strength of 66 MPa, indicating insufficient strength.
[0082] In addition, the machinability of J (Reference Comparative Example 6), a denture base PET resin that does not fall under the category of specific polyester, was evaluated as △, with the resin melting to the cutting bar many times during cutting. In addition, the polishability was evaluated as ×, with numerous polishing scratches visually confirmed. Furthermore, the bending strength was 81 MPa, a lower value compared to Reference Examples 1 to 4.
[0083] Furthermore, the polishing property of K (Reference Comparative Example 6), which is a denture base polyester resin not corresponding to the specific polyester, was evaluated as ×, and numerous polishing scratches were visually confirmed. Furthermore, the bending strength was 75 MPa, which was a lower value compared with Reference Examples 1 to 4.
[0084] 2. Examples 1 to 13 and Comparative Examples 1 to 5 Next, the thermoplastic resin for dentures of the present invention will be described with reference to examples and comparative examples, but the present invention is not limited thereto. Evaluation samples used in the examples and comparative examples were prepared by press molding using a thermoplastic resin composition prepared by blending the following commercially available thermoplastic resins alone or in a specified combination and ratio, and the adhesiveness to (meth)acrylate-based hard lining materials and silicone-based soft lining materials was evaluated. Details are shown below.
[0085] 2-1.Thermoplastic resin (1) Specific polyester The above E to H. That is, E: Altesta SN1500 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) F: Altesta SN3000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) G: Altesta SN4500 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) H: Artesta SH (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0086] (2)Specified amorphous resin L: Rigid polyvinyl chloride (Sun-Arrow Chemical Co., Ltd. Rigid Sanar Compound SC-2100) M: Polystyrene (GPPS HF77 manufactured by PS Japan Co., Ltd.) N: PMMA (Acrypet VH001 manufactured by Mitsubishi Chemical Corporation) O: ABS (Stylac 026 manufactured by Asahi Kasei Corporation) P: Polycarbonate (Teijin Ltd. Panlite L-1225Y) Q: Polycarbonate made from isosorbide (DURABIO D7340 manufactured by Mitsubishi Chemical Corporation) R: Modified polyphenylene ether (Iupiace AH80 manufactured by Mitsubishi Engineering Plastics Corporation) · S: Glycol modified polyethylene terephthalate (PET-G GN071 manufactured by Eastman Chemical Company).
[0087] (3) Amorphous thermoplastic resins other than specific amorphous resins (hereinafter also referred to as "non-specific amorphous resins") T: Polysulfone (Ultrason S2010 manufactured by BASF Europe) · U: Cycloolefin polymer (ZEONEX 790R manufactured by Zeon Corporation).
[0088] In addition, whether the amorphous thermoplastic resin corresponds to a specific amorphous resin or is not To determine whether a particular ATR is a specific amorphous resin, a pellet of each ATR was immersed in 1 ml of ethyl acetate at 37°C for 24 hours, and visually observed. Dissolution Those that were partially dissolved and the shape collapsed or a clear volume expansion due to swelling was observed were rated as ◎, those that were partially dissolved and the shape collapsed or a clear volume expansion due to swelling was observed were rated as ○, those that were only cloudy were rated as △, and those that showed no change at all were rated as ×. Those that were rated as ◎ or ○ were classified as specific amorphous resins, and those that were rated as △ or × were classified as non-specific amorphous resins. For reference, the evaluation results of the solubility or swelling of various ATRs in ethyl acetate, as well as the deflection temperature under load and flexural strength are shown in Table 3.
[0089] [Table 3]
[0090] 2-2. Preparation of evaluation samples Each vacuum-dried resin was used as is (Comparative Example 1) or mixed (Examples 1 to 13 and Comparative Examples 2 to 5) to obtain the composition shown in Table 4, and then melt-kneaded and pelletized. Specifically, a twin-screw extrusion kneader (HAAKE process 11 manufactured by Thermo Fisher Scientific) was used, and melt-kneaded at a barrel temperature of 280°C, a die temperature of 240°C, and a screw rotation speed of 50 rpm to 150 rpm, and the discharged blended resin was cooled with water and then pelletized using a pelletizer.
[0091] Next, the obtained pellets were used in a heating press (IMC-11D2-C, manufactured by Imoto Machinery Co., Ltd.) and a SUS mold to produce smooth, bubble-free plate-shaped test pieces 1, 2 cm square and 5 mm thick; smooth plate-shaped test pieces 2, 15 mm x 30 mm and 2 mm thick; and smooth plate-shaped test pieces 3, 15 mm x 30 mm and 2 mm thick.
[0092] 2-3.Evaluation method (1) Evaluation of adhesion to (meth)acrylate-based hard lining materials The plate-shaped test piece 1 was adhered to a SUS plate 1.5 cm square and 2 mm thick, and the surface of the resin was polished with #800 waterproof abrasive paper to prepare an adherend. Tokuyama Rebase III Normal (Tokuyama Dental Co., Ltd.) was used as the (meth)acrylate-based hard backing material, and the adhesive was a rebase adhesive (Tokuyama Dental Co., Ltd.), an ethyl acetate-containing primer. A double-sided tape with a hole of 3 mm in diameter was attached to the surface of the adherend to define the adhesive area, and the rebase adhesive was applied with a brush. On top of that, a 0.5 mm thick paraffin wax with a hole of 8 mm in diameter was attached so as to be concentric with the hole of 3 mm in diameter, to form a simulated restoration part. A rice cake-like material obtained by kneading the powder and liquid of Tokuyama Rebase III Normal to a P / L ratio of 1.7 was filled into the simulated restoration part, and then lightly pressed with a polypropylene film from above. The test pieces were left in a humid environment at 37°C for 1 hour to harden Tokuyamari Base III Normal, and then immersed in water at 37°C for 24 hours. A metal attachment to be used in tensile tests was attached to the Tokuyamari Base III Normal of the removed test pieces. The tensile strength was measured by setting the test pieces in a precision universal testing machine (AG-Xplus50kN, manufactured by Shimadzu Corporation) and using a crosshead speed of 2mm / min. Five measurements were made for one sample, and the average value was taken as the tensile strength.
[0093] (2) Evaluation of adhesion to silicone-based soft lining materials The surface of the plate-shaped test piece 2 was polished with #800 waterproof abrasive paper to prepare a set of two adherends. Softliner Tough Medium (manufactured by Tokuyama Dental Co., Ltd.) was used as the silicone-based soft lining material, and the included adhesive primer, which is an ethyl acetate-containing primer, was used as the adhesive. The adhesive primer included with Softliner Tough Medium was thinly and uniformly applied to the surfaces of the two adherends with a disposable brush. A 3 mm thick fluororesin (polytetrafluoroethylene) mold with a hole of 10 mm in diameter was placed on one of the two adherends to prepare a simulated repair part. Softliner Tough Medium was mixed with a mixing tip and filled into the simulated repair part, and the adhesive-coated side of the other adherend was placed on top of it so that it was in contact with the lining material, and pressed together. The test piece was left in a humid environment at 37°C for one hour to harden the Softliner Tough Medium, and then immersed in water at 37°C for 24 hours. After that, the metal attachments used in the tensile test were attached to the top and bottom of the removed test piece, i.e., to both back sides of the adherend. To measure the tensile strength, the test piece was set in a precision universal testing machine (AG-Xplus50kN, manufactured by Shimadzu Corporation), and the metal attachments were used to perform a tensile test on both sides at a crosshead speed of 5mm / min. Four measurements were performed for one sample, and the average value was taken as the tensile strength. In this test, the upper limit of the tensile strength is a low value of about 2.0 to 3.0 MPa. This is because it is derived from the strength of the soft backing material used in the test. Therefore, it is appropriate to judge the adhesion in this test based on the fracture form. When the adhesion is good, the soft backing material undergoes bulk fracture, and when the adhesion is insufficient, interfacial fracture occurs between the adherend and the soft backing material, so the adhesion was evaluated based on whether it was bulk fracture or interfacial fracture.
[0094] (3) Bending strength measurement The plate-shaped test piece 3 was used to carry out the bending strength measurement in the same manner as in the reference example.
[0095] 2-4.Evaluation results The evaluation results of the examples and comparative examples are shown in Table 4. In Table 4, "addition amount" refers to the blended amount (parts by mass) of the amorphous thermoplastic resin (specific amorphous resin or non-specific amorphous resin) relative to 100 parts by mass of the specific polyester.
[0096] [Table 4]
[0097] As shown in Table 4, in Examples 1 to 13 using the thermoplastic resin composition for dentures of the present invention, the adhesion to the lining material is improved while maintaining the inherent characteristics of the specific polyester, as is clear from a comparison with Comparative Example 1. In contrast, in Comparative Examples 2 and 3 in which a non-specific amorphous resin was blended, no such effect of improving adhesion to the lining material was observed. In Comparative Example 4 in which 1 part by mass of the specific amorphous resin was blended with 100 parts by mass of the specific polyester, no effect of improving adhesion was observed, and in Comparative Example 5 in which 50 parts by mass of the specific amorphous resin was blended, a significant decrease in physical properties was observed.
Claims
1. A thermoplastic resin composition for a denture base used as a material for a denture base, comprising: Thermoplastic polyester resin: 100 parts by mass and amorphous thermoplastic resin: 5 to 25 parts by mass, The thermoplastic polyester resin is a polyester resin obtained by polycondensing a diol component (A) and a dicarboxylic acid component (B) in a ratio of 1 mol:1 mol, the polyester resin having a deflection temperature under load of 85 to 125°C as measured in accordance with the B method of JIS standard K7191-2:2007 and a Rockwell hardness of 90 to 120 as measured in accordance with the L scale of JIS standard K7202-2:2001, The diol component (A) contains a spiro glycol (A1) having a cyclic acetal skeleton and ethylene glycol (A2), the contents of (A1) and (A2) based on the total number of moles of all diol compounds contained in the diol component (A) are, respectively, (A1): 15 to 95 mol % and (A2): 5 to 85 mol % or less, and the total content of (A1) and (A2) is 20 to 100 mol % or less, The dicarboxylic acid component (B) is Contains a dicarboxylic acid compound (B1) having a polycyclic aromatic hydrocarbon skeleton and / or an ester (B1') thereof, the total content of the (B1) and the (B1') is 15 to 100 mol % based on the total number of moles of all dicarboxylic acid compounds contained in the dicarboxylic acid component (B), The amorphous thermoplastic resin is At least one selected from the group consisting of polyvinyl chloride, polystyrene, polymethyl methacrylate, acrylonitrile-butadiene-styrene copolymer resin, polycarbonate, modified polyphenylene ether, and glycol-modified polyethylene terephthalate, The deflection temperature under load measured according to JIS K7191 Method A is in the range of 60 to 150°C. A thermoplastic resin composition for denture base, comprising:
2. 2. The thermoplastic resin composition for denture base according to claim 1, wherein the dicarboxylic acid compound (B1) is naphthalenedicarboxylic acid.
3. 3. The thermoplastic resin composition for denture base according to claim 1 or 2, wherein the amorphous thermoplastic resin is at least one selected from the group consisting of polystyrene, polymethyl methacrylate, and acrylonitrile-butadiene-styrene copolymer resin, and is soluble in ethyl acetate.
4. The dentures have a partial base with artificial teeth fixed thereto, and clasps for attaching the dentures to the clasps. At least a part of the partial base and the clasp are made of a molded body of the thermoplastic resin composition for denture bases according to any one of claims 1 to 3. A non-metal clasp denture.
Citation Information
Patent Citations
Thermoplastic resin composition and molding
JP2001214078A
Polyester resin
JP2005002237A
Polyester resin injection molded article
JP2008260964A
Polyester resin composition
JP2010018729A
Decorative film
JP2011219667A
